from a handpicked tutor in LIVE 1-to-1 classes

# Choose the equation that could be used to find three consecutive integers whose sum is 36.

n + (n + 2) + (n + 4) = 36

n + (n + 1) + (n + 3) = 36

n + (n + 1) + (n + 2) = 36

n + (n - 1) + (n - 3) = 36

**Solution: **

We have to find three consecutive integers whose sum is 36.

From the given option,

1) n + (n + 2) + (n + 4) = 36

So, 3n + 6 = 36

3n = 36 - 6

3n = 30

n = 30/3

n = 10

n + 2 = 10 + 2 12

n + 4 = 10 + 4 = 14

So, the numbers are 10, 12, 14.

Since, the numbers are not consecutive. Option(1) is not true.

2) n + (n + 1) + (n + 3) = 36

Now, 3n + 4 = 36

3n = 36 - 4

3n = 32

n = 32 / 3

n + 1 = 32 / 3 + 1 = 35 / 3

n + 3 = 32 / 3 + 3 = 41 / 3

So, the numbers are 32/3, 35/3 and 41/3

The numbers are not consecutive. Therefore, Option(2) is not true.

3) n + (n + 1) + (n + 2) = 36

So, 3n + 3 = 36

3n = 36 - 3

3n = 33

n = 33/3

n = 11

n + 1 = 11 + 1 = 12

n + 2 = 11 + 2 = 13

The numbers are 11, 12 and 13.

The numbers are consecutive. Therefore, option(3) is true.

4) n + (n - 1) + (n - 3) = 36

So, 3n - 4 = 36

3n = 36 + 4

3n = 40

n = 40/3

n - 1 = 40 / 3 - 1 = 37 / 3

n - 3 = 40 / 3 - 3 = 31 / 3

The numbers are 40 / 3, 37 / 3 and 31 / 3.

The numbers are not consecutive. Therefore, option(4) is not true.

Therefore, the three consecutive integers are 11, 12 and 13.

## Choose the equation that could be used to find three consecutive integers whose sum is 36.

**Summary:**

The equation that could be used to find three consecutive integers whose sum is 36 is n + (n + 1) + (n + 2) = 36.

visual curriculum